Characterisation of chondrocyte matrix responses under biaxial loading / Illida Mohd Nawi - Illida, Mohd Nawi (2011)
In vivo, during mechanical loading, articular cartilage is exposed to a complex biophysical environment. These biophysical and biochemical concepts have not yet been fully understood due to intricate combination of direct, shear and tensile compressive strains on articular cartilage. Mechanical forces and deformations are sensed by cells and turned into biochemical signals; which evolution is essential in regulating chondrocyte function; both in metabolic and catabolic modus operandi. The main objective of this study is to investigate the influence of biaxial loading on chondrocytes. This thesis will also describe the strain rate influence of biaxial loading on chondrocytes in 3D agarose scaffold in different types of waveform. Prior to the core studies, an optimized protocol to harvest the highest numbers of viable cells was obtained. These allow the preparation of a sufficient quantity of cells for high seeding density, which in turn promotes the expression of normal chondrocytic phenotype and facilitates cartilage repair. This study modulated parameters such as collagenase type, enzymatic duration and collagenases‟ concentration in order to obtain the highest cell yield and viability. From this study, maximum cell yield was harvested from the two-step digestion with 1-hour digestion of protease and 16-hour in collagenase type-II, without jeopardizing their viability. Cell yield obtained with this protocol was 14 million cells per ml (±0.41% SEM) and cell viability of 97.5% (±0.19% SEM). Consequently, obtained chondrocytes were seeded in 4% three-dimensional agarose constructs. Seeded constructs were exposed to cyclic loading of 10% direct compressive and/nor 1% shear strain(s) to see the effect of biaxial and uniaxial loadings. A novel-designed bioreactor was used to deliver the loads. The load was delivered for two 12 hours-blocks, at a frequency of 1Hz, with 12 hours resting period in the middle. The incubator-housed bioreactor is used to give various types of waveforms to the constructs. The suspension was analyzed for DNA content using Hoechst 33258 dye with calf thymus DNA as a standard. GAG was measured with DMB assays and chondroitin-4-sulphate was used as the reference solution. The need for pre-culturing before exposure to biaxial loading was also examined. Predominantly, chondrocytes favoured to be pre-cultured for 24 hours upon seeding before being subjected to any load and prefer biaxial loading to increase GAG levels. Biaxial loading shows stimulatory effect on matrix synthesis with 1.5-fold increase in GAG production of chondrocytes upon being exposed to biaxial loading vs. uniaxial loading. Nevertheless, chondrocytes seem to favour for sinusoidal loading when it comes to proteoglycans synthesis. This study has moved research into the effects of mechanical loading on cartilage regeneration a step forward. Due to the complex structure of cartilage – anisotropy and heterogeneity, articular cartilage subjected to mechanical loading has been shown to activate multiple regulatory pathways; upstream signalling, transcription, post-translational modification and vesicular transport. Mechanical loading such as simultaneous matrix stretch and compression facilitates transportation of molecules and nutrients. Signalling mechanisms due to cyclic loading involve the actin cytoskeleton, stretch-activated ion channels and activation of tyrosine kinase.